Globalization and the rise of mega-cities in the developing world - Frederick van der Ploeg; Steven Poelhekke (Center for Economic Studies and ifo Institute (CESifo), 2008)
Thomas Friedman has argued in The World is Flat that those who deny rapid globalization will not survive in the global economy. First, we critically discuss Friedman's views and highlight the new globalization driven by outsourcing and vertical specialization. Second, we argue that Friedman pays insufficient attention to the spectacular growth of mega-cities in the developing world. The world is not flat, and the developing world certainly is not. Still, mega-cities tend to become too big. Their growth also goes hand in hand with formation of slums and congestion. We thus argue that there is a role for public policies.
Keywords: F01; H40; O10; R10; 330; globalization; unbundling; off-shoring; mega-cities; congestion; public policies; Globalisierung; Agglomerationseffekt; Ballungsraum; Offshoring; Bottleneck; Makroökonomischer Einfluss; Entwicklungsländer